First record of the Zebra Grasshopper Zebratula (Acrididae: Catantopini) in Queensland, Australia - Connors, Matthew G. (Zootaxa, 2023)
Australia’s grasshopper fauna is among the most distinctive in the world, and yet the majority of species remain undescribed, and there is still much to learn even about relatively well-documented genera and species. Here I present the first record of the genus Zebratula, the Zebra Grasshoppers, in Chillagoe (Queensland), representing a range extension of almost 900 km. Additionally, I comment on the specific identity of this specimen and the likelihood that it represents an undescribed species, as well as discuss the importance of Chillagoe as a biodiversity hotspot.